Annual Plan 1966-67 Orissa - Planning Commission (Planning Commission, 1966)
State Plan- Head of Development, Outlay and Progress., Centrally Sponsored Schemes—Heads of Development, Outlay and Progress., State Plan—Scheme-Wise Outlay and Progress., Agricultural Programmes, Community Development and Co-operation, Irrigation and Power, Industry and Mining, Transport and Communication, Social Services.
Orissa